When Differential Descending Control of Speed Matters: Descending Modulation of A- versus C-Fiber Evoked Spinal Nociception - Lumb, Bridget M.; Donaldson, Lucy F. (Frontiers in Pain Research, 2022)
Descending pain modulatory systems (DPMS) that originate within the brain and act to modulate spinal nociceptive transmission are a major determinant of the acute and chronic pain experience (1). Investigations of these systems in basic scientific research is critical to the development of therapeutic strategies for the relief of pain. Despite our best efforts, something is lost in translation. This article will explore whether this is due in part to a primary focus on sensory modality leading to a failure to differentiate between descending control of A- versus C-fibre mediated spinal nociception.